2005
DOI: 10.1309/ph7x78hf4fw4prkw
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Large Granular Lymphocyte Leukemias Have Multiple Phenotypic Abnormalities Involving Pan–T-Cell Antigens and Receptors for MHC Molecules

Abstract: T-cell large granular lymphocyte (T-LGL) leukemias represent monoclonal T-cell expansions that express CD16, CD56, or CD57 and cause cytopenias. The identification of T-LGL leukemias can be difficult because reactive T-LGL cells also can express CD16, CD56, and CD57, and many leukemia cases show only mild lymphocytoses. In this study, 23 T-LGL leukemia cases were analyzed by 3- and 4-color flow cytometry to identify markers that could aid in discriminating leukemic from normal T-LGL. In most cases (18/23), abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(24 citation statements)
references
References 31 publications
2
20
0
2
Order By: Relevance
“…For instance, in NK and T‐cell large granular lymphocytosis lymphocytes often express activating or inhibitory KIRs in a clonal manner 225, 226, 227, 228. Patients with Sezary syndrome typically display CD4 + T cells expressing KIR3DL2, which might contribute to disease onset 228, 229.…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…For instance, in NK and T‐cell large granular lymphocytosis lymphocytes often express activating or inhibitory KIRs in a clonal manner 225, 226, 227, 228. Patients with Sezary syndrome typically display CD4 + T cells expressing KIR3DL2, which might contribute to disease onset 228, 229.…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…Leukemic proliferation has an aberrant immunophenotype.CD5 and CD7 are most commonly downregulated antigens [11]. NK cell associated antigens like CD16 and CD57 are expressed in 80 and 100 % of the cases respectively.…”
Section: Discussionmentioning
confidence: 99%
“…10,18 Others have detailed specific bone marrow immunohistochemical criteria for defining cases of T-LGL leukemia with detailed statistical analyses. 8 However, a statistically powered study of cases of LGL expansions to determine the significance of variations in antigen expression by flow cytometry has not been performed to date.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior studies have demonstrated distinct histologic features associated with T-LGL leukemia in the marrow 8 as well as novel TCR antibodies that can be used to define LGL leukemia, 9 relatively few studies have attempted to comprehensively and statistically define the specifics of non-TCR antigen expression by flow cytometry. 10,11 As such, we performed a detailed retrospective review of 85 patients, at Stanford University Medical Center, with LGL expansions in their peripheral blood in an attempt to determine distinct flow cytometry patterns that are associated with T-LGL leukemia.…”
Section: Introductionmentioning
confidence: 99%